ANALISIS KESADARAN HUKUM MASYARAKAT GUNA MEWUJUDKAN KETERTIBAN DAN KEAMANAN DALAM BERMASYARAKAT, BERBANGSA DAN BERNEGARA (STUDI KASUS DI DESA KWARAKAN KECAMATAN KALORAN KABUPATEN TEMANGGUNG) - Wardani, Sri Mustika; Kristiana, Lindra; Kuntarti, Rita; Mega, Aryanti (JURNAL DWIJA KUSUMA, 2023)
Legal awareness must be embedded in every human being without an exception in order to create social order, orderliness, peace and harmony live within the society. Therefore, the commitment of Indonesians to design a legal awareness society program has been possessed a long time; various ways and businesses has been done, in the process and even continue to do it which is all in the hope of creating the legal supremacies we hope for. This research attempts to analyze the certain extent development of the law-conscious society, particularly in Kwarakan village, Kaloran Sub District of Temanggung, in its responsible for the establishment of national security and social order in society. This study uses purpose sampling which means researchers deliberately select respondents who have the responsibility and authority in explaining the investigated problem. The Data collection method is implemented by the spreading questionnaires, interviews and observations. According to the data obtained, it can be stated that the current level of awareness of the law in Kwarakan village is relatively good. The percentage results indicate 47.8 % people's legal awareness is good while 39.1 % is relatively good, while 13.1 % of the people need to be improved. The factors that affect in increasing the people’s legal awareness based on the data that we're getting in Kwarakan Village are principally highly associated to social, economics, education, religion factors; family roles. The needs of legal counseling, environmental factors as well as legal sanctions for offenders are important.